Organic Mulching Alters the Soil Microclimate, Increases Survival and Growth of Tree Seedlings in Restoration Planting - Machado, Deivid Lopes (2024)
Organic mulching has been suggested as an option for managing spontaneous species in restoration plantings and can promote improvements in soil properties and performance of planted species. The aim of this study was to test the effect of crowning techniques on soil microclimatic and performance of forest seedlings. The experiment was carried out in Goiás state, Brazil. Two study factors were used: crowning techniques (manual weeding, cardboard, wood chipping and control—without weed competition management), and six tree species: Anadenanthera peregrina, Ceiba speciosa, Dipteryx alata, Inga edulis, Genipa americana and Spondias mombin. Soil temperature and moisture assessments were performed within the crowning area (0.25 m2). Seedling survival and growth in height and diameter were evaluated over 219 days. Organic mulching treatments of wood chipping and cardboard provided increase in soil moisture and decrease in temperature, resulting in higher seedling survival rate. The increase in height and diameter differed among species under study, with A. peregrina standing out in height and C. speciosa in diameter. The crowning techniques did not influence the average height of species; however, wood chipping provided greater diameter increase. The findings of this study indicate that mulching treatments, by contributing to increase soil moisture and decrease soil temperature, can be used as crowning techniques to increase the survival rate and diameter growth of tree species in restoration plantings.